Research on scenario-based mechanism in privacy-aware mobile networks - Ben NIU; Feng-hua LI; Jia-feng HUA; Yuan-yuan HE (网络与信息安全学报)
The well-developed information services has infiltrated in each part of our daily life,various novel ser-vice modes and applications provide us conveniences at the cost of our privacy.This situation becomes more serious with the increasing number of applications and users’ requirements.The privacy issues of scenario-based mechanism in mobile networks have been studied based on analyzing the state-of-the-art research trends.The threat and chal-lenges of privacy disclosure caused by the mobile network services,and review the scenarios,service models and attack models were introduced firstly.Followed,a comprehensive study on current status of background information,quality of services,and resource-restricted related privacy preservation were made.Finally,some key technologies on privacy preservation such as background information modeling and descripting,multi-background information fusion,quality of services descripting and modeling,self-adaptive methods based on historical information,pri-vacy-preserving solutions optimizing energy resources and privacy-preserving schemes equalizing multiple factors etc were posted.